Green infrastructure design for transport projects a road map to protecting Asias wildlife biodiversity. (Asian Development Bank, 2019)
Asia harbors immense biodiversity that is increasingly threatened by expanding transport networks across the region. While considered essential for economic development and human activity, roads and railways are widely regarded as a primary driver for the rapid loss of natural ecosystems and living species. This report details the variety of green infrastructure and other conservation measures available from environmentally sensitive road design to animal passage structures and management guidelines to reduce transport project impacts on wildlife.